2013
DOI: 10.4097/kjae.2013.64.2.127
|View full text |Cite
|
Sign up to set email alerts
|

Small dose of propofol combined with dexamethasone for postoperative vomiting in pediatric Moyamoya disease patients: a prospective, observer-blinded, randomized controlled study

Abstract: BackgroundFor effective postoperative antiemetic management in pediatric moyamoya disease patients receiving fentanyl based postoperative analgesia, a multimodal approach has been recommended. The uncertain efficacy of ondansetron for pediatric neurosurgical patients or the possible antiemetic effect of small dose of propofol motivated us to evaluate the preventive effect of a subhypnotic dose of propofol combined with dexamethasone on postoperative vomiting (POV), especially during immediate postoperative per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
(31 reference statements)
0
3
1
Order By: Relevance
“…In contrast to the previous study [ 16 ], there was the prolongation of emergence time in the propofol 0.5 and propofol 1.0 groups compared to the control group (P < 0.05). However, prolonged time was only 2.6-3.4 minutes, and it may not be significant in clinical practice.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to the previous study [ 16 ], there was the prolongation of emergence time in the propofol 0.5 and propofol 1.0 groups compared to the control group (P < 0.05). However, prolonged time was only 2.6-3.4 minutes, and it may not be significant in clinical practice.…”
Section: Discussioncontrasting
confidence: 99%
“…Another study showed that 1.0 mg/kg of propofol at the end of surgery reduced both PONV and emergence agitation in children [ 6 ]. On the other hand, Kim et al [ 16 ] reported that 0.5 mg/kg of propofol combined with dexamethasone was not effective in the prevention of PONV in pediatric patients with moyamoya disease.…”
Section: Discussionmentioning
confidence: 99%
“…In a small study, the P value may not reach statistical significance, even when there is a clinically relevant difference in a given baseline characteristic. For example, as shown in Table 2 [6], patient ages are not statistically different (8.1 [3.4] versus 10.0 [3.9]; P = 0.052). However, an almost 2-year gap in a group of pediatric patients could have a meaningful effect on the result in a clinical situation.…”
Section: Pre-occupation With P Values For Baseline Characteristicsmentioning
confidence: 99%
“…Respectively, 31, 60, 67, 17, 31, and 35 of the 312 RCTs reported P values for comparisons of ASA, height, weight, BMI, duration of anesthesia and surgery. Eighty-three (26.5%) studies reported P values in baseline data tables, among which 6 [611] reported P values that were statistically significant (i.e., < 0.05). Descriptions such as “similar” or “comparable” in the article were not considered as significant.…”
Section: P Values Published In the Kjamentioning
confidence: 99%